1999
DOI: 10.1182/blood.v93.1.341
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Specific Activation of Distinct Mitogen-Activated Protein Kinase Subtype Cascades in Human Neutrophils Stimulated by Granulocyte Colony-Stimulating Factor, Granulocyte-Macrophage Colony-Stimulating Factor, and Tumor Necrosis Factor-

Abstract: To clarify the differences of the signaling pathways used by granulocyte colony-stimulating factor (G-CSF), granulocyte-macrophage colony-stimulating factor (GM-CSF), and tumor necrosis factor- (TNF), we investigated activation of mitogen-activated protein kinase (MAPK) subtype cascades in human neutrophils stimulated by these cytokines. G-CSF exclusively tyrosine-phosphorylated extracellular signal-regulated kinase (ERK). GM-CSF tyrosine-phosphorylated ERK strongly and p38 MAPK weakly, whereas TNF tyrosine-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(79 citation statements)
references
References 30 publications
10
68
0
1
Order By: Relevance
“…The MAPK mediate diverse functions such as cell division and degranulation in various cell types. TNF stimulation of neutrophils activates all three MAPK: ERK1/2, Jun N-terminal kinase, and p38 MAPK [24]. p38 MAPK and ERK1/2 have been shown to be involved in the degranulation of granulocytes [25,26]; however, we have previously demonstrated that inhibiting p38 with SB203580 has no effect on TNF-induced MMP-9 release [20].…”
Section: Erk1/2 Is Not Critical For Tnf-induced Mmp-9 Release From Nementioning
confidence: 89%
“…The MAPK mediate diverse functions such as cell division and degranulation in various cell types. TNF stimulation of neutrophils activates all three MAPK: ERK1/2, Jun N-terminal kinase, and p38 MAPK [24]. p38 MAPK and ERK1/2 have been shown to be involved in the degranulation of granulocytes [25,26]; however, we have previously demonstrated that inhibiting p38 with SB203580 has no effect on TNF-induced MMP-9 release [20].…”
Section: Erk1/2 Is Not Critical For Tnf-induced Mmp-9 Release From Nementioning
confidence: 89%
“…These findings are consistent with our recent studies showing that ERK is selectively activated in human neutrophils stimulated by G-CSF, and ERK is involved in G-CSF-induced neutrophil migration. 3,14 The role of ERK in cell migration has also been demonstrated in various cell lines, and ERK-mediated activation of myosin light chain kinase and calpain 2 (m-calpain) is proposed to be involved in the stimulation of cell migration. 17,18 In human neutrophils, it has been recently reported that calpain 1 (l-calpain) functions as a negative regulator in cell migration by inhibiting the activation of Cdc42 and Rac, 19 and calpain 2 is a component of the frontness signal that promotes polarization during chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Human neutrophils were prepared from healthy adult donors, as described previously, 3 using dextran sedimentation, centrifugation with Conray-Ficoll and hypotonic lysis of contaminating erythrocytes. Neutrophil fractions contained more than 98% neutrophils.…”
Section: Preparation Of Cellsmentioning
confidence: 99%
“…Human peripheral blood neutrophils were prepared from healthy adult donors as described previously [13], using dextran sedimentation, centrifugation with Conray-Ficoll, and hypotonic lysis of contaminating erythrocytes. Neutrophil fractions were suspended in HBSS containing 10 mM HEPES (pH 7.4) and contained more than 95% neutrophils, and contaminating cells were almost exclusively eosinophils.…”
Section: Preparation Of Cellsmentioning
confidence: 99%